Transformasi Pemasaran Tradisional Ke Digital Marketing: Analisis Peluang dan Tantangan pada Make Up Artist (MUA) Di Kota Bandung - Resti Waliyani; Fauziah Nurcahya; Laesya Syifa F; Yani Iriani (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The transformation of marketing strategies from conventional methods to digital marketing has become an important factor in the development of the beauty industry, especially for Make Up Artists (MUAs) in Bandung. This study aims to analyze the impact of digital marketing through social media on increasing customer interest and the number of MUA service users, with a case study of Iwan Haadi, a professional MUA in Bandung who is active on Instagram (@iwanhaadimakeup) and TikTok (@iwanhaadi). This research employs a descriptive qualitative method with a case study approach, using interviews, observations of social media activities, and documentation of digital promotional content. The results show that before implementing digital marketing, MUAs generally relied on conventional promotions such as word of mouth and collaborations with wedding organizers. However, technological developments have encouraged many MUAs to shift to social media to expand their promotional reach. Based on observations of Iwan Haadi and 20 other MUAs in Bandung, around 85% have utilized social media particularly Instagram and TikTok to showcase their portfolios and client testimonials. The implementation of digital marketing strategies has proven to increase brand awareness and the number of customers by up to 65% over the past two years. In conclusion, digital marketing has a significant influence on increasing customers and competitiveness among MUAs in Bandung. Consistent and creative use of social media is the key to attracting customer interest and strengthening a professional image in the modern beauty industry.